2022
DOI: 10.52006/main.v5i2.490
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Psychosocial Impact of Lockdown and Life Satisfaction Assessment of Nigerian Working Adults during Coronavirus Pandemic

Abstract: The study assessed the perceived psychosocial impact of lockdown and life satisfaction of Nigerian working adults during the coronavirus pandemic. A cross-sectional research design was adopted, and 518 working adults participated in the study using the convenience sampling technique. Two sets of questionnaires served as the data collection instruments. Data generated from the study were analyzed using mean, standard deviation, and OLS regression analysis. Results revealed, amongst others, that relationships wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Though, African nations have begun to revitalize higher education before the emergence of the COVID-19, but the pandemic scaled down most of the efforts (Mohamedbhai, 2020). The pandemic affected nearly all higher institutions in the African continent due to the abrupt closure of academic activities, to curb the spread of the virus and this led to consequential disruption in students' learning (Itasanmi, Ojedeji, & Ekpenyong, 2022). The COVID-19 crises, therefore, exacerbated longstanding Africa's meagre national and institutional capacities to manage higher education and persistent continuation of the crises indicated that various governments' commitment toward higher education in the continent may be severely affected in the face of other competing priority sectors, that are critical to vulnerable segments of the society (Tamrat & Teferra, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Though, African nations have begun to revitalize higher education before the emergence of the COVID-19, but the pandemic scaled down most of the efforts (Mohamedbhai, 2020). The pandemic affected nearly all higher institutions in the African continent due to the abrupt closure of academic activities, to curb the spread of the virus and this led to consequential disruption in students' learning (Itasanmi, Ojedeji, & Ekpenyong, 2022). The COVID-19 crises, therefore, exacerbated longstanding Africa's meagre national and institutional capacities to manage higher education and persistent continuation of the crises indicated that various governments' commitment toward higher education in the continent may be severely affected in the face of other competing priority sectors, that are critical to vulnerable segments of the society (Tamrat & Teferra, 2020).…”
Section: Introductionmentioning
confidence: 99%